Lipase-Catalyzed Synthesis of Wax Ester - Mat Hadzir, Nursyamsyila (2001)
Alcoholysis reaction between triolein and oleyl alcohol catalyzed by Lipozyme and Novozyme was carried out to produce oleyl oleate, a wax ester. Several reaction parameters were studied in order to get its optimal condition such as effect of time, reaction temperature, amount of enzyme, molar ratio of substrates (oleyl alcohol/trioleib), various organic solvents used, initial water activity (aw), continuously controlled water activity and addition of silica gel. The optimal condition to produce wax ester for Lipozyme are incubation time of 5 h, temperature of 50°c and using 30% (w/v) of Lipozyme. The molar ratio of substmte was 6:1 (oleyl alcohol/triolein) in heptane and at aw 0.33 (initial water activity) or 0.32 (continuously controlled water activity) with the addition of 0.25 g of silica gel. For Novozyme, the optimum incubation time was 5 h, at reaction temperature of 60 °c using 30% (w/v) of Novozyme. The optimum molar ratio of substrates (oleyl alcohol/triolein) was also at 6:1, in heptane at aw 0.33 (initial water activity, aw), 0.32 (continuously controlled water activity) and with the addition of 0.50 g of silica gel. A scale up reaction was then carried out using the optimum condition catalyzed by Lipozyme. The percentage yield of wax ester produced at optimum reaction condition was 58.48% when determined by gravimetry method and 75.66% when determined using gas chromatography.